The Influence Internal Market on Service Quality at the Land Office of North Lombok Regency, Indonesia (Global Journal of Management and Business Research, 2018)
Up to now, the topic of the demand for improving the quality of public services in the management of government becomes a major demand for the improvement of service performance of the state apparatus is increasingly felt and important, because the good service and the prime will have an impact on the realization of a clean and authoritative government climate. One of the strategic policies of the Indonesian government is to improve the quality of public services. In the implementation of public services is often not in accordance with what is expected by the people who always want excellent service quality. Lots of public complaints that the quality of public services is very low and even disappointing. Similarly, those happened in government service agencies including, the Land Office of North Lombok Regency as a new Office, always striving to improve and provide the best services to all communities in the land sector. The purpose of this study is to analyze the influence of recruitment, training and motivation on Service Quality at the Land Office of North Lombok regency. In this research use quantitative approach by using technique of Multiple Linear Regression analysis. The results of this study showed silmultan significant effect on the quality of service. Motivation is the most dominant variable influencing Service Quality at the Land Office of North Lombok regency. Head of the Land Office of North Lombok Regency should improve the quality of service by improving the training and motivation of its employees.
Keywords: recruitment; training; motivation and quality of services